Fibrosis, the Bad Actor in Cardiorenal Syndromes: Mechanisms Involved - Beatriz Delgado-Valero; Victoria Cachofeiro; Ernesto Martínez-Martínez (Cells, 2021)
Cardiorenal syndrome is a term that defines the complex bidirectional nature of the interaction between cardiac and renal disease. It is well established that patients with kidney disease have higher incidence of cardiovascular comorbidities and that renal dysfunction is a significant threat to the prognosis of patients with cardiac disease. Fibrosis is a common characteristic of organ injury progression that has been proposed not only as a marker but also as an important driver of the pathophysiology of cardiorenal syndromes. Due to the relevance of fibrosis, its study might give insight into the mechanisms and targets that could potentially be modulated to prevent fibrosis development. The aim of this review was to summarize some of the pathophysiological pathways involved in the fibrotic damage seen in cardiorenal syndromes, such as inflammation, oxidative stress and endoplasmic reticulum stress, which are known to be triggers and mediators of fibrosis.